EDUCATIONAL INTERVENTION ON EARLY MOBILIZATION COMPLIANCE AMONG POST-CESAREAN MOTHERS - Nidya Comdeca Nurvitriana; Karunia Wijayanti; Devi Maya (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Many mothers lack awareness of the benefits of early mobilization following caesarean section (post-Sc). This study aimed to assess the influence of educational intervention on early mobilization among post-Sc mothers at RSAD Level III Brawijaya Surabaya, utilizing a pre-experimental design with a single cohort. The sample consisted of 43 mothers who underwent caesarean section from December 2023 to January 2024, selected through purposive sampling. Early mobilization served as the dependent variable, with education as the independent variable. Results revealed a positive shift post-education, with 20 participants (47%) improving from the